Analisis Pengaruh Religiusitas, Pengetahuan Halal, Norma Subjektif, dan Online Customer Review terhadap Niat Beli Makanan Jepang pada Konsumen Muslim di Purwokerto - Ai Sinta Rosita; Tri Septin Muji Rahayu; Suyoto Suyoto; Totok Haryanto (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of religiosity, halal knowledge, subjective norms, and online customer reviews on the purchase intention of Japanese food among Muslim consumers in Purwokerto. The study used a quantitative approach with a survey method of 160 respondents selected through purposive sampling. The research instrument was a 5-point Likert-scale questionnaire, and the data were analyzed using multiple linear regression. The results showed that the variables of religiosity, halal knowledge, subjective norms, and online customer reviews had a positive and significant influence on the purchase intention of Japanese food among Muslim consumers in Purwokerto.